Asthma and fixed airflow obstruction: Long‐term trajectories suggest distinct endotypes. Issue 1 (14th August 2020) - Smith, Benjamin M.; Zhao, Nan; Olivenstein, Ronald; Lemiere, Catherine; Hamid, Qutayba; Martin, James G.
Abstract: Background: Long‐term trajectories of asthma with fixed airflow obstruction (FAO) may reveal links to inflammatory endotypes. Objective: We investigated whether measures of asthma control and airway inflammation and remodelling differed by long‐term FAO status in moderate‐to‐severe asthma. Methods: Adults enrolled in the Difficult Asthma Study assessed initially using serial Asthma Control Questionnaire (ACQ), exacerbation history, spirometry and sputum cytology over 12 months, as well as endoscopic bronchial biopsy with airway smooth muscle (ASM) quantification, were revaluated three or more years later with questionnaires and spirometry. FAO was defined as a persistent post‐bronchodilator forced expired volume in one second (FEV1 )‐to‐forced vital capacity ratio below 0.70. Results: Sixty‐two participants (mean ± SD age 48 ± 11 years; 50% female; 75% atopic; asthma duration 24 ± 14 years) returned for follow‐up assessment (median interval 7.9 years; IQR: 5.4‐8.8 years). Compared to participants without FAO (n = 28), those with FAO at baseline and long‐term follow‐up (n = 18) had higher baseline sputum neutrophil content and ASM, and a higher exacerbation frequency that persisted at long‐term follow‐up. Sputum eosinophils, ACQ and long‐term FEV1 decline did not differ. Participants with incident FAO at long‐term follow‐up (n = 16) had higher baseline exacerbation frequency, sputum eosinophil content, higher ACQ scores and greater decline in FEV1, whereas baseline ASM was similar to those without FAO. Conclusion: In moderate‐to‐severe asthma, long‐term FAO is characterized by neutrophilic sputum inflammation and airway remodelling, but FEV1 decline is similar to those without FAO. Long‐term incident FAO is preceded by higher exacerbation frequency, higher sputum eosinophil content and significant FEV1 decline.